Creation of Computerized 3D MRI-Integrated Atlases of the Human Basal Ganglia and Thalamus - Sadikot, Abbas F.; Chakravarty, M. Mallar; Bertrand, Gilles; Rymar, Vladimir V.; Al-Subaie, Fahd; Collins, D. Louis (Frontiers in Systems Neuroscience, 2011)
Functional brain imaging and neurosurgery in subcortical areas often requires visualization of brain nuclei beyond the resolution of current Magnetic Resonance Imaging (MRI) methods. We present techniques used to create: 1) a lower resolution 3D atlas, based on the Schaltenbrand and Wahren print atlas, which was integrated into a stereotactic neurosurgery planning and visualization platform (VIPER); and 2) a higher resolution 3D atlas derived from a single set of manually segmented histological slices containing nuclei of the basal ganglia, thalamus, basal forebrain and medial temporal lobe. Both atlases were integrated to a canonical MRI (Colin27) from a young male participant by manually identifying homologous landmarks. The lower resolution atlas was then warped to fit the MRI based on the identified landmarks. A pseudo-MRI representation of the high-resolution atlas was created, and a nonlinear transformation was calculated in order to match the atlas to the template MRI. The atlas can then be warped to match the anatomy of Parkinson’s disease surgical candidates by using 3D automated nonlinear deformation methods. By way of functional validation of the atlas, the location of the sensory thalamus was correlated with stereotactic intraoperative physiological data. The position of subthalamic electrode positions in patients with Parkinson’s disease was also evaluated in the atlas-integrated MRI space. Finally, probabilistic maps of subthalamic stimulation electrodes were developed, in order to allow group analysis of the location of contacts associated with the best motor outcomes. We have therefore developed, and are continuing to validate, a high-resolution computerized MRI-integrated 3D histological atlas, which is useful in functional neurosurgery, and for functional and anatomical studies of the human basal ganglia, thalamus and basal forebrain.